2021
DOI: 10.2991/assehr.k.210716.022
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Commitment and Culture on Teacher Job Satisfaction: A Regression Analysis

Abstract: This study aims to determine the effect of organizational commitment and organizational culture on teacher job satisfaction. This research was conducted in SD Negeri Babat Supat District, Musi Banyuasin Regency, Indonesia. The number of samples of this study was 75 teachers, who were taken using probability sampling techniques, and were calculated using the Slovin formula. Data collection using a questionnaire. Testing data using linear regression analysis techniques. The results of data analysis show that: (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…Furthermore, the dimension đť‘ť 42 was .0216 or 2.16 %, indicating that the effect of OC on JS is low. Another study found that organizational culture positively affected teacher's job satisfaction (Supriyati et al, 2021). The finding corresponds with the analysis presented by Azanza et al (2013).…”
Section: Findings and Discussionsupporting
confidence: 81%
“…Furthermore, the dimension đť‘ť 42 was .0216 or 2.16 %, indicating that the effect of OC on JS is low. Another study found that organizational culture positively affected teacher's job satisfaction (Supriyati et al, 2021). The finding corresponds with the analysis presented by Azanza et al (2013).…”
Section: Findings and Discussionsupporting
confidence: 81%